The Influence of First Language Toward Students' Achievement in Learning English - Siti Sarah Fitriani; Dwi Rahayu Prasetyaningsih; Iskandar Abdul Samad (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2017)
In an English as a Foreign Language (EFL) classroom, most of the time the teacher cannot avoid the use of mother tongue in teaching and learning activities. This happens in some countries whose English is not their native language, including Indonesia. This paper examines the influence of first language used by a teacher in an Indonesian EFL classroom. The teacher and six tenth graders from a science classroom were involved in this study. Semi-structured interviews were conducted to gather in-depth data. The data were then analysed qualitatively based on the steps by Miles and Huberman (1984): data reduction, data display and data conclusion or verification. The findings indicate the teacher’s and the students’ perspectives on the use of first language in EFL classroom. Most of the students agreed the teacher includes the first language in their English classroom as it positively helps them in learning the target language. In addition, the teacher supports the students’ view because the inclusion of the first language in EFL classroom is considered a way to solve the students’ problem in learning the target language